Metodologia para avaliação do impacto do treinamento em pesquisa bibliográfica: um estudo no campus saúde da Universidade Federal de Minas Gerais - Mariza Cristina Torres Talim (2015)
Currently libraries are also places of teaching and learning by offering training that enable users to use the information retrieval systems in different areas of knowledge. These trainings have meaning only if they are effective for developing information literacy in users. The objective of this study is to evaluate the impact of training, with load of 15 hours, in literature search in MEDLINE database and Search Portal of BVS in information seeking behavior of postgraduate students and residents of the Health Campus in Federal University of Minas Gerais. From the point of view of its nature we conducted a descriptive basic research with typical procedures of a case study approach using both quantitative and qualitative. The research used a non-random sample consisting of the masters and residents who agreed to participate in the training. The research used various instruments to collect data to verify the changes in the first three levels of Kirkpatrick's training evaluation model. A questionnaire was administered at the beginning of training to identify the profile, the experience and seeking behavior of the participating students. Another questionnaire applied at the end of training, repeated questions about the informational seeking behavior of the first questionnaire to assess the impact of training on information behavior of students. A third questionnaire on critical incident was answered by students between four and five months after the end of the training to assess the impact of training in professional activities and educational activities of students. It was also used two tests, given at the beginning and end of the training, evaluating student performance in conducting a search. The research results indicate a significant positive impact, verified by the reaction of the participants of the training, the demonstration of new knowledge and research skills. The knowledge and skills demonstrated by students at the end of training were transferred to their professional and educational activities.